2006
DOI: 10.1037/1064-1297.14.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and erectile response: The effects of high dosage in the context of demands to maximize sexual arousal.

Abstract: Although drinking is often associated with men's sexual activity, basic questions about alcohol's effects on men's sexual arousal remain unanswered. Inconsistencies in findings from studies examining subjective and physiological effects on erectile functioning suggest that alcohol's effects are context specific, e.g., dependent on whether one wants to maximize or suppress his arousal. To address unresolved questions about alcohol and erectile functioning, two experiments evaluated the effects of high blood alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 42 publications
1
31
1
1
Order By: Relevance
“…In the context of our vignette, alcohol could "disinhibit" subjective sexual arousal by reducing attention to inhibitory cues and thereby resulting in an intensified focus on cues impelling an erotic response. In contrast, the stimulus materials utilized in the George et al (2006) study were largely devoid of inhibitory cues. Under such low-conflict conditions, the Inhibition Conflict Model of AMT would predict null effects for alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of our vignette, alcohol could "disinhibit" subjective sexual arousal by reducing attention to inhibitory cues and thereby resulting in an intensified focus on cues impelling an erotic response. In contrast, the stimulus materials utilized in the George et al (2006) study were largely devoid of inhibitory cues. Under such low-conflict conditions, the Inhibition Conflict Model of AMT would predict null effects for alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Fast Fourier Transform (FFT) analyses were then applied to the artifact-free data in 2-s epoch samples, with the spectral graph ranging from 0.5 -30 Hz at 0.5 Hz-resolution. FFTs were performed using EEGmagic software [38] to calculate: 1) absolute power (AP), defined as the power density of each frequency band expressed in microvolts squared (μV2/Hz); 2) relative power (RP), the proportional contribution of each band to total power across 1 -30 Hz and; 3) correlation, the degree of functional coupling between the prefrontal and parietal or temporal cortices in each one of the six frequency bands monitored: namely, delta (1 -3.5 Hz), theta (4 -7.75 Hz), alpha1 (8 -10.5 Hz), alpha2 (11 -13.5 Hz), beta1 (14 -19.5 Hz) and beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Correlation values were averaged over all epochs of the same condition for each subject and pair of derivations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of erotic films in eliciting sexual arousal in humans [21][22][23] using both, questionnaires or verbal reports as well as objective measures (changes of the penile circumference) [24,25]. Associated with this sexual arousal state induced by observation of erotic films, characteristic EEG changes has been reported, such as increases in the fast frequencies and decreases in the synchronization between cortical areas of young men [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Three measurements were obtained: percentage of average circumferential increase of the penis in mm, time in seconds that it takes to achieve an increase of 5% in mm circumference compared to the average of previous Neutral Stimuli (NS), and period above 5% increase. A 5% increase in mm circumference was used as threshold as was done previously George et al (2006).…”
Section: Responses Evaluatedmentioning
confidence: 99%
“…Studies are observed which evaluate different types of sex offenders, including child molesters (Marshall & Marshall, in press;Michaud & Proulx, 2009), rapists Looman and Marshall (2005), sexual sadists (Marshall & Yates, 2004;Proulx, Blais, & Beauregard, 2006) and exhibitionists Kolářský and Madlafousek (1983). Other studies have measured the effect of substance use on sexual response (George et al, 2006;Harte, 2014),distractions to sexual stimuli Anderson and Hamilton (2014), cognitive mechanisms linked to arousal Both, Laan, and Everaerd (2011) or implications of arousal in condom use Janssen et al (2014). All these aspects are relevant to sexual health, and it is important to have reliable and valid assessment methods, as this may impact theory testing, decisions regarding the effectiveness of a psychological treatment, experimental verification of the impact of one or more independent variables, etc.…”
Section: Introductionmentioning
confidence: 99%